Working conditions – a factor for retaining and attracting highly qualified human capital - Dimitrova, Mariana (Leadership, Society, Strategic Visions, 2021)
In the dynamically changing modern world, work and employment call for a new approach on the behalf of the employers and society, as well as for rethinking of the meaning we put into the concept of job quality and job wellbeing. Competition for highly qualifi ed professionals on an European and on a global scale transforms working conditions into one of the key aspects that make an position attractive. It is also one of the key factors for developing and retaining talented professionals. The paper contains an analysis of data and guidelines for the development of the concept of working conditions in the Republic of Bulgaria as a model for improving workplaces and making them desired by Bulgarian citizens, by the Bulgarians emigrants abroad and by the foreigners seeking employment in the Bulgarian economy.